Radionuclides and sedimentation rates of sediment cores from the eastern South Atlantic, supplementary data to: Frank, Martin; Gersonde, Rainer; Rutgers van der Loeff, Michiel M; Kuhn, Gerhard; Mangini, Augusto (1996): Late Quaternary sediment dating and quantification of lateral sediment redistribution applying 230Th-excess, a study of the eastern Atlantic sector of the Southern Ocean. Geologische Rundschau, 85(3), 554-566 - Frank, Martin; Gersonde, Rainer; Rutgers van der Loeff, Michiel M (PANGAEA - Data Publisher for Earth & Environmental Science, 1996)
High-resolution records of the natural radionuclide 230Th were measured in sediments from the eastern Atlantic sector of the Antarctic circumpolar current to obtain a detailed reconstruction of the sedimentation history of this key area for global climate change during the late Quaternary. High-resolution dating rests on the assumption that the 230Thex flux to the sediments is constant. Short periods of drastically increased sediment accumulation rates (up to a factor of 8) were determined in the sediments of the Antarctic zone during the climate optima at the beginning of the Holocene and the isotope stage 5e. By comparing expected and measured accumulation rate of 230Thex, lateral sediment redistribution was quantified and vertical particle rain rates originating from the surface water above were calculated. We show that lateral contributions locally were up to 6.5 times higher than the vertical particle rain rates. At other locations only 15% of the expected vertical particle rain rate were deposited.